Pengembangan Website E-Commerce dengan Pemanfaatan Sistem Payment Gateway Midtrans (Studi Kasus: Butik Rizza Collection) - Chairunisa Dwinanda Asti; Widhy Hayuhardhika Nugraha Putra; Welly Purnomo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Rizza Collection boutique is one of the boutiques in the city of Malang that provides a variety of Muslim products with many variations and contemporary models. In addition, this boutique also opens production to order clothing on request according to customer wishes. However, until now, the request for clothing is still ordered by visiting the boutique directly. In promoting products and online transactions, it is done through social media, so that payments are made manually. The payment and ordering mechanism for the clothing request has not been effective. To further facilitate transaction activities at the Rizza Collection Boutique, an e-commerce website that is integrated with the Midtrans payment gateway has been developed. Customers will find it easier to make payments without having to confirm to the admin, as well as make it easier to order clothing requests without having to come directly to the boutique. In doing development, analysis and design are needed to determine functional and non-functional requirements on the system, namely using UML diagrams and database design using Physical Data Model (PDM). The development of this system is carried out using the waterfall model, CodeIgniter DBMS MySQL framework. Testing is carried out using the blackbox testing method to get 100% valid results, which means the system can run according to the specified requirements analysis, compatibility testing obtains that the system is compatible so that it can be run on various types of browsers, User Acceptance Testing (UAT) gets the final result with a percentage value of 91.77%, it can be concluded that the system developed can be accepted by the user with the results strongly agree.